Ocular and perineal squamous cell carcinomas in a Holstein Friesian cow - Jiashi Feng; Helène Larde; Ailbhe King; Dylan Thomas; Georgios Paraschou; Pompei Bolfa (Open Veterinary Journal)
Background: Squamous cell carcinoma (SCC) in domestic cattle is an economically significant malignant neoplasm and has been documented primarily in ocular and periocular tissues, vulva and perineum. SCCs are often slow-growing and locally invasive, but metastasis is uncommon. Increased risk of developing SCC has been predominantly associated with high levels of sunlight exposure and hypopigmentation (skin and conjunctiva). This manuscript reports a case of ocular and perineal SCC in a Holstein Friesian cow with maxillary sinusitis secondary to tumor invasion.